2008
DOI: 10.1073/pnas.0711345105
|View full text |Cite
|
Sign up to set email alerts
|

In vivo diffusion of lactoferrin in brain extracellular space is regulated by interactions with heparan sulfate

Abstract: The intercellular spaces between neurons and glia contain an amorphous, negatively charged extracellular matrix (ECM) with the potential to shape and regulate the distribution of many diffusing ions, proteins and drugs. However, little evidence exists for direct regulation of extracellular diffusion by the ECM in living tissue. Here, we demonstrate macromolecule sequestration by an ECM component in vivo, using quantitative diffusion measurements from integrative optical imaging. Diffusion measurements in free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(142 citation statements)
references
References 50 publications
2
139
1
Order By: Relevance
“…A great many studies using a wide variety of tracer substances and multiple different ex vivo/in vivo methods have concluded that the local transport of small and large molecules through the brain ECS of the neuropil is predominantly diffusive in nature; such studies have included ventriculo-cisternal or subarachnoid-cisternal perfusion of radiolabelled tracers [111,135,144], real-time iontophoresis of the small tetramethylammonium ion [126], and integrative optical imaging (IOI) of pressure-injected fluorescently labelled molecules [127,[178][179][180]191]. Electron microscopy studies focused on neuropil ultrastructure have long indicated a brain ECS width of approximately 10-20 nm [21,75,81,136] and, importantly, that these narrow spaces could be accessed with tracers such as HRP (40 kDa) following intracerebroventricular injection [20,21].…”
Section: Diffusion or Flow Of The Isf In The Brain Ecs?mentioning
confidence: 99%
See 1 more Smart Citation
“…A great many studies using a wide variety of tracer substances and multiple different ex vivo/in vivo methods have concluded that the local transport of small and large molecules through the brain ECS of the neuropil is predominantly diffusive in nature; such studies have included ventriculo-cisternal or subarachnoid-cisternal perfusion of radiolabelled tracers [111,135,144], real-time iontophoresis of the small tetramethylammonium ion [126], and integrative optical imaging (IOI) of pressure-injected fluorescently labelled molecules [127,[178][179][180]191]. Electron microscopy studies focused on neuropil ultrastructure have long indicated a brain ECS width of approximately 10-20 nm [21,75,81,136] and, importantly, that these narrow spaces could be accessed with tracers such as HRP (40 kDa) following intracerebroventricular injection [20,21].…”
Section: Diffusion or Flow Of The Isf In The Brain Ecs?mentioning
confidence: 99%
“…The polyanionic nature and binding capacity of the ECM may significantly impact the diffusion of certain ions and other molecules in the brain ECS (e.g., confinement or binding of ions by perineuronal nets [76] or chondroitin sulphate proteoglycans [83], sequestration of growth factors [173], and protein binding to heparan sulphate proteoglycans [179]). CSF-ISF exchange of molecules is, therefore, expected to be limited by (1) molecular size, (2) ECM interactions, (3) receptor binding, (4) aggregation state (e.g., certain pathogenic proteins), (5) permeability characteristics (e.g., clearance across the BBB), and (6) distance from the brain-CSF interface, and likely other factors.…”
Section: Csf and Isf Compartmentalization And Drainage Pathwaysmentioning
confidence: 99%
“…In addition to geometric hindrance mediated by cellular obstacles, morphogen movement might be further hindered by transient binding to extracellular molecules, such as morphogen receptors or extracellular matrix components (Crank, 1979;Lander et al, 2002;Baeg et al, 2004;Belenkaya et al, 2004;Han et al, 2004;Lin, 2004;Han et al, 2005;Callejo et al, 2006;Hufnagel et al, 2006;Thorne et al, 2008;Wang et al, 2008;Miura et al, 2009;Yan and Lin, 2009;Müller and Schier, 2011;Müller et al, 2012;Sawala et al, 2012). In the drunken sailor analogy, sailors frequently linger in pubs along the way (Fig.…”
Section: Binding-mediated Hindrancementioning
confidence: 99%
“…In contrast to the free diffusion model, which posits that geometric effects from cells on diffusion are negligible or that movement occurs outside of the cell field, hindered diffusion postulates that cell packing, and hence tortuosity (see Box 2), strongly influences the movement of extracellular molecules. Extracellular morphogens must go around cells and this reduces their overall dispersal (Nicholson and Syková, 1998;Rusakov and Kullmann, 1998;Nicholson, 2001;Tao and Nicholson, 2004;Thorne and Nicholson, 2006;Thorne et al, 2008). In the drunken sailor analogy, sailors perform random walks in a region containing buildings, not in a large empty lot (Fig.…”
Section: Tortuosity-mediated Hindrancementioning
confidence: 99%
“…It also exhibits antioxidant activities and has both anticarcinogenic and anti-inflammatory properties (Garcia-Montoya et al, 2012). While iron chelation is directly responsible for some of the biological functions of lactoferrin, other activities require interactions of lactoferrin with cell-specific receptors located on target cells (Suzuki et al, 2005;Pierce et al, 2009) or with molecular and cellular components of both hosts and pathogens, including heparan sulfate proteoglycans (HSPGs) (Thorne et al, 2008;Lang et al, 2011) and bacterial lipopolysaccharides (Drago-Serrano et al, 2012).…”
Section: Introductionmentioning
confidence: 99%